Integrating the rural poor into markets - Debroy, Bibek; Khan, Amir Ullah; International Development Enterprises (India); India Development Foundation (New Delhi : Academic Foundation published in association with India Development Foundation (IDF) and International Development Enterprises, India, 2004)
Contributed articles with special reference to economic aspects of agriculture in India.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- India; Rural poor -- India; Rural development -- India